2021
DOI: 10.1007/s40747-021-00351-8
|View full text |Cite
|
Sign up to set email alerts
|

Solving knapsack problems using a binary gaining sharing knowledge-based optimization algorithm

Abstract: This article proposes a novel binary version of recently developed Gaining Sharing knowledge-based optimization algorithm (GSK) to solve binary optimization problems. GSK algorithm is based on the concept of how humans acquire and share knowledge during their life span. A binary version of GSK named novel binary Gaining Sharing knowledge-based optimization algorithm (NBGSK) depends on mainly two binary stages: binary junior gaining sharing stage and binary senior gaining sharing stage with knowledge factor 1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Other recent work by [138] addresses the knapsack problem by utilizing a binary gaining sharing knowledgebased optimization algorithm. The Gaining Sharing Knowledge-based (GSK) optimization algorithm addresses binary optimization problems based on the concept of acquisition and sharing of knowledge of humans during their lifetime.…”
Section: Trajectory-based Algorithms (Tbas)mentioning
confidence: 99%
“…Other recent work by [138] addresses the knapsack problem by utilizing a binary gaining sharing knowledgebased optimization algorithm. The Gaining Sharing Knowledge-based (GSK) optimization algorithm addresses binary optimization problems based on the concept of acquisition and sharing of knowledge of humans during their lifetime.…”
Section: Trajectory-based Algorithms (Tbas)mentioning
confidence: 99%
“…To verify the performance of the two algorithms, i.e., DEHLO1 and DEHLO2, the proposed DEHLOs as well as other six binary-coding optimization algorithms, i.e., Improved Adaptive Human Learning Optimization (IAHLO) [ 37 ], Simple Human Learning Optimization (SHLO) [ 34 ], Modified Binary Differential Evolution (MBDE) [ 47 ], Novel Binary Differential Evolution (NBDE) [ 53 ], Improved Binary Particle Swarm Optimization (IBPSO) [ 54 ], and Novel Binary Gaining Sharing Knowledge-based optimization (NBGSK) [ 17 ], were applied to solve multidimensional knapsack problems [ 55 ]. The parameters pr, pi, CR, F, and b adopt the default values of HLO and MBDE, and a set of fair parameters, i.e., Cn and K of DEHLO1 and NM and NH of DEHLO2, is chosen for DEHLO1 and DEHLO2 by trial and error in this paper, that is, Cn = 100, K = 5%, NM = 100, and NH = 50.…”
Section: Resultsmentioning
confidence: 99%
“…Metaheuristics are general frameworks to build heuristics for combinatorial and global optimization problems [ 3 ]. The application of natural or biology-inspired metaheuristic optimizations, such as Genetic Algorithm [ 4 ], Particle Swarm Optimization [ 5 ], Harmony Search [ 6 ], Differential Evolution (DE) [ 7 – 10 ], Artificial Bee Colony [ 11 ], Fruit Fly Optimization [ 12 ], Distributed Grey Wolf Optimizer (DGWO) [ 13 ], Moth Search Algorithm (MSA) [ 14 ], Slime Mould Algorithm (SMA) [ 15 ], Gaining Sharing Knowledge-Based Optimization [ 16 , 17 ], Cuckoo Search with Exploratory (ECS) [ 18 ], Discrete Jaya with Refraction Learning and Three Mutation (DJRL3M) [ 19 ], and Monarch Butterfly Optimization (MBO) [ 20 ], Hunger Games Search (HGS) [ 21 ], Runge Kutta Method (RUN) [ 22 ], and Harris Hawks Optimization (HHO) [ 23 ], has been very successful to solve the complex optimization problems, such as feature selection [ 24 28 ], image segmentation [ 29 ], controller designation [ 30 ], flow-shop scheduling problem [ 31 , 32 ], and the node placement of wireless sensor networks [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…They observed that GSK algorithm gives significantly better results as compared to other metaheuristic algorithms in terms of accuracy, convergence, and can find the optimal solutions. Moreover, Agrawal et al [37][38][39][40] proposed binary versions of the GSK algorithm and applied it to the real-world problems such as feature selection problem, knapsack problem.…”
Section: Figure 1: Classification Of Metaheuristic Algorithmsmentioning
confidence: 99%